A new strategy for osteoarthritis therapy: Inhibition of glycolysis - Tan, Chunmei; Li, Lanqing; Han, Juanjuan; Xu, Kang; Liu, Xianqiong (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a common degenerative disease of the joints. It is primarily caused by age, obesity, mechanical damage, genetics, and other factors, leading to cartilage degradation, synovial inflammation, and subchondral sclerosis with osteophyte formation. Many recent studies have reported that glycolysis disorders are related lead to OA. There is a close relationship between glycolysis and OA. Because of their hypoxic environment, chondrocytes are highly dependent on glycolysis, their primary energy source for chondrocytes. Glycolysis plays a vital role in OA development. In this paper, we comprehensively summarized the abnormal expression of related glycolytic enzymes in OA, including Hexokinase 2 (HK2), Pyruvate kinase 2 (PKM2), Phosphofructokinase‑2/fructose‑2, 6‑Bisphosphatase 3 (PFKFB3), lactate dehydrogenase A (LDHA), and discussed the potential application of glycolysis in treating OA. Finally, the natural products that can regulate the glycolytic pathway were summarized. Targeting glucose transporters and rate-limiting enzymes to glycolysis may play an essential role in treating OA.